2009
DOI: 10.1007/s12576-009-0079-x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulates central and peripheral responses to cold in female rats

Abstract: The aim of this study was to determine whether estrogen modulates central and peripheral responses to cold in female rats. In ovariectomized female rats with and without administered estrogen [E(2) (+) and E(2) (-), respectively], the counts of cFos-immunoreactive cells in the medial preoptic nucleus (MPO) and dorsomedial hypothalamic nucleus (DMH) in the hypothalamus were greater in the E(2) (+) rats than in the E(2) (-) rats at 5 degrees C. Examination of the response of normal female rats to exposure to 5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
(52 reference statements)
3
18
0
1
Order By: Relevance
“…In addition, the sympathetic nerve stimulates brown adipose tissue to cause non-shivering thermogenesis. It is reported that estrogen acts on the hypothalamus and brown adipose tissue and affects thermoregulation (9,29). In the present study, changes in central body temperature during general anesthesia were observed.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, the sympathetic nerve stimulates brown adipose tissue to cause non-shivering thermogenesis. It is reported that estrogen acts on the hypothalamus and brown adipose tissue and affects thermoregulation (9,29). In the present study, changes in central body temperature during general anesthesia were observed.…”
Section: Discussionsupporting
confidence: 50%
“…Uchida et al assessed the effect of estradiol on thermoregulation by comparing ovariectomized rats that did and did not receive estradiol replacement. They suggested that estradiol lessens the reduction in core temperature during cold exposure by affecting autonomic and behavioral thermoregulatory processes [13,14]. The influence of estradiol on heart rates has also been reported in female rats: they demonstrate tachycardia after the depletion of plasma estradiol [15][16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…Depletion of plasma estradiol and progesterone starts within an hour after surgical removal of the ovaries in rats [23]. To assess the influence of estradiol depletion, previous studies have compared ovariectomized animals to sham-operated/estradiol-dosed animals [13,14,24] or investigated animals with genetic depletion of estradiol or estradiol receptors [25]. However, these studies could not clarify the time-effect after the estradiol depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mechanisms of impaired adaptive thermogenesis in Pacap-deficient mice following cold exposure Molecular experiments were performed only on male mice, as estrous cycle patterns and sexual hormones in female rodents are known to impact thermoregulatory responses (Bu & Lephart 2005, Uchida et al 2010. This experiment was conducted in two independent batches of male Pacap K/K and Pacap , 4 8C) as described above.…”
Section: Experimental Procedures Ne-induced Thermogenesis Inmentioning
confidence: 99%